Assessment of Fuel Wood Energy Demand of Arba Minch Town, Gamo Gofa Zone, Southern Ethiopia - Bekele, Bayisa; Ugo, Yonas; Chauhan, Rajesh (International Journal of Bio-resource and Stress Management, 2021)
The current rate of deforestation in Ethiopia is exacerbated by number of factors including increased rate of population, increased fuel wood consumption, urbanization, infrastructure development, etc. However, fuel wood energy requirement is one of the major problems causing deforestation. The current study was conducted during 2017 with the objective to estimate the fuel wood consumption of Arba Minch Town. To achieve this objective a household survey was conducted in the town. Out of 11 kebeles of the town four were selected purposely. 58 household respondents were selected for the study. People of the area using fuel wood for various purposes such as cooking, for lighting and for selling as source of income. Arba Minch forest is the source of fuel wood for majority of the households. On average basis, single house hold is using 4.01 kg of fuel wood day-1. The fuel wood consumption of other user such as hotels, govt. institutions were also recorded by conducting survey in four sub cities. Among different user group of fuel wood in the town fuel wood consumption by individual HHs were maximum (66 t day-1 or 24090 t year-1) followed by hotels (2.65 t day-1 or 969.08 t year-1) and lowest by government institutes (110 t day-1 or 40.15 t year-1). Thus, total consumption of fuel wood in Arba Minch town is 68.78 t day-1 or 25,099.23 t year-1. The demand for fuel wood consumption is in increasing trend. This growing demand of fuel wood from household is posing a threat to the remaining natural forest and associated wildlife and resources. Therefore, it is recommended that there is a need of adoption of alternative sources of energy which can replace fuel wood energy. Thus community participation in forest protection should be encouraged and illegal consumption of fuel wood in the study area should be checked.